Schauspiel und Roman im Zeichen des modernen politischen Zionismus: Wolfgang von Weisl: Erlöser, Der Anfang der Wandlung Israels - Goltschnigg, Dietmar (2020)
This third volume, which concludes a research project on the Viennese Zionist Wolfgang von Weisl and his family history, generously funded by the Austrian Science Fund (FWF), presents two historical and fictional works written by him: the play Erlöser and the novel Der Anfang der Wandlung Israels, whose central figures, Simon Bar Kochba und Josepf Trumpeldor - the latter immigrated from Russia to Palestine - are still present in Israel's collective memory as glorified national heros and martyrs.